Corruption in Public Procurement in Ghana: societal norm or deviant behaviour? - Dza, Mawuko; Kyeremeh, Evan; Dzandu, Simon S. K.; Afran, Samuel (Archives of Business Research, 2018)
The paper probes corruption in public procurement in Ghana. The research, which focused on Metropolitan, Municipal and District Assemblies (MMDAs) across the country, revealed widespread corruption in the public service of Ghana. Notable procurement related corrupt practices unraveled included influence peddling, inflating contract sums, payment for non-existing contracts, deliberate contract splitting, multiple payments for contracts, use of phantom vendors and misapplication of public funds. The study further noted that some principal officers such as Coordinating Directors, Finance Officers, Budget and Planning officers, Engineers, Internal Auditors, Stores and Procurement officers, as well as government representatives misappropriate funds meant for development projects in their catchment areas, while staff looked on unconcerned. The research also discovered how Internal and external auditors ostensibly “train” principal officers on how to conceal corrupt practices in return for money and other rewards. The study is significant because the concept of decentralization was introduced to enable MMDAs to effectively and efficiently manage resources for the development of their communities. The concept has been defeated as some public servants connive with external auditors and other stakeholders to amass wealth at the expense of the generality of the people. A worrying phenomenon is the culture of silence by employees who are witnesses to most of these corrupt practices. Indeed, our findings show that most public servants are nonchalant about the act of corruption perpetuated by colleague workers. Essentially, some employees see nothing wrong with their principal officers and other colleagues indulging in acts of corruption, their reason being that they might do same when they assume similar positions in future. With this revelation, the onus is on government not to only adopt a combative strategy in dealing with the incidence of corruption. Rather, it is recommended that a blend of combative and the moral suasion strategies be adopted if the fight against corruption is to achieve desired results.